2020
DOI: 10.1177/2050312120910359
|View full text |Cite
|
Sign up to set email alerts
|

Challenges associated with physical assessments for people living with dementia: Modifying standard assessment protocols

Abstract: Objectives: Regular physical activity for older adults as they age is important for maintaining not only physical function but also independence and self-worth. To be able to monitor changes in physical function, appropriate validated measures are required. Reliability of measures such as the timed-up-and-go, five-repetition sit-to-stand, handgrip strength, two-minute walk, 30-second sit-to-stand, and four-metre walk has been demonstrated; however, the appropriateness of such measures in a population of adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A paper reporting the outcomes has recently been published. 24 From the perspective of partners-in-care, the program resulted in greater improvement than deterioration postintervention for all factors measured, and not necessarily associated with physical function. Changes in perception of who might benefit from participation in such a program were evident; however, there was still a perception that residents who are most severely declined will not benefit from participation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…A paper reporting the outcomes has recently been published. 24 From the perspective of partners-in-care, the program resulted in greater improvement than deterioration postintervention for all factors measured, and not necessarily associated with physical function. Changes in perception of who might benefit from participation in such a program were evident; however, there was still a perception that residents who are most severely declined will not benefit from participation.…”
Section: Discussionmentioning
confidence: 93%
“…Such concerns led to trialing modified protocols for the assessments as a part of the study reported here, with a subset of our participants. A paper reporting the outcomes has recently been published …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations